Comparison of running and accelerometry variables based on match outcome, match location and quality of opponent in elite professional soccer players. A five-season study - Ryland Morgans; John Radnor; Jose Fonseca; Dave Rhodes; Ben Ryan; Matthew King; Piotr Zmijewski; Rafael Oliveira (Biology of Sport)
The aim of this study was to compare external match load, according to match outcome, match location, and opponent quality across five competitive seasons. Forty-six professional outfield soccer players from the same English Premier League club across the complete 2018/19 to 2022/23 seasons were involved in the study. For each match, the outcome (win, draw, loss), match location (home, away) and quality of opponent (top or bottom six teams, remaining mid-table teams) were recorded. Players covered significantly more m/min and performed more decelerations when playing against the top six compared to mid-table or bottom six teams ( p < 0.001; d = 0.213–0.322). There were no differences in external match load depending on match outcome. There were significant opponent × outcome × match location interactions for each position across most of the external match load measures, but these differed in magnitude for specific metrics and positions ( p = 0.001–0.048; d = 0.300 1.741). The present study provided novel information on external match load and the influence of match outcome, match location and opponent quality. This may support and contribute to understanding how to improve training methods to physically prepare players to cope with varying contexts.